IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Trya Khaerunisa; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of the Merdeka Curriculum in elementary schools through a Systematic Literature Review (SLR) approach. The implementation of the Merdeka Curriculum has become an important issue in the transformation of education in Indonesia because it emphasizes student-centered learning, differentiated instruction, and the strengthening of the Pancasila Student Profile. This study aims to analyze the implementation of the Merdeka Curriculum in elementary schools, particularly regarding teacher readiness, learning strategies, assessment, implementation barriers, and its impact on student learning outcomes. The research employed a qualitative descriptive approach using the Systematic Literature Review (SLR) method. Data sources were obtained from 25 national journals indexed by SINTA and reputable international journals relevant to the topic. Data collection techniques were carried out through documentation studies and literature searches from academic databases, while data analysis used content analysis techniques through data reduction, classification, interpretation, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum positively contributes to improving students' creativity, critical thinking skills, active participation, and independent learning. However, several obstacles remain, including limited teacher understanding, low digital literacy, and inadequate learning facilities. This study contributes theoretically to strengthening the literature on curriculum implementation and practically provides recommendations for educators and policymakers to improve the effectiveness of the Merdeka Curriculum in elementary education.